2013
DOI: 10.1111/febs.12321
|View full text |Cite
|
Sign up to set email alerts
|

Novel glyoxalases from Arabidopsis thaliana

Abstract: We examined six Arabidopsis thaliana genes from the DJ-1/PfpI superfamily for similarity to the recently characterized bacterial and animal glyoxalases. Based on their sequence similarities, the six genes were classified into two sub-groups consisting of homologs of the human DJ-1 gene and the PH1704 gene of Pyrococcus horikoshii. Unlike the homologs from other species, all the A. thaliana genes have two tandem domains, which may have been created by gene duplication. The six AtDJ-1 proteins (a-f) were express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(103 citation statements)
references
References 49 publications
6
97
0
Order By: Relevance
“…Although the specific reason for these differences is unclear, our results indicate that Hsp31-like proteins are considerably more active methylglyoxalases than human DJ-1. This conclusion is consistent with a recent report on the glyoxalase activities of several A. thaliana members of the DJ-1 superfamily, which found that the closest homologs of human DJ-1 in that organism (AtDJ-1A and AtDJ-1B) have only modest glyoxalase activity (61). Therefore, it remains to be established if the glyoxalase activities of human DJ-1 and its close homologs are physiologically relevant.…”
Section: Discussionsupporting
confidence: 91%
“…Although the specific reason for these differences is unclear, our results indicate that Hsp31-like proteins are considerably more active methylglyoxalases than human DJ-1. This conclusion is consistent with a recent report on the glyoxalase activities of several A. thaliana members of the DJ-1 superfamily, which found that the closest homologs of human DJ-1 in that organism (AtDJ-1A and AtDJ-1B) have only modest glyoxalase activity (61). Therefore, it remains to be established if the glyoxalase activities of human DJ-1 and its close homologs are physiologically relevant.…”
Section: Discussionsupporting
confidence: 91%
“…Oxidative Stress-The glyoxalase system consists of two enzymes, GLY1 and GLY2, involved in methylglyoxal (MG) detoxification, though novel glyoxalases have been recently described (65). MG is produced in all living organisms and its levels in plants are enhanced on exposure to different abiotic stresses (66).…”
Section: Discussionmentioning
confidence: 99%
“…cDJR - 1.1 is found in both the nucleus and cytoplasm of the intestine, while cDJR - 1.2 is detected in various tissues and is only present in the cytoplasm [6]. The Arabidopsis thaliana genome has six DJ - 1 genes, among which AtDJ - 1d encodes an enzyme that has the highest GLO3 activity [46]. Besides, a close homolog of HsDJ-1 called SpDJ-1 (Accession number: SPAC22E12.03c) has been found in the fission yeast Schizosaccharomyces pombe [41].…”
Section: Introductionmentioning
confidence: 99%